Using kinematic measures to predict post flight time in the women`s artistic gymnastics straight twisting Yurchenko vault - Edginton, R. (World Congress of Performance Analysis of Sport IX, 2012)
The aim of this study was to investigate kinematic parameters of the Yurchenko vault in elite level competition. The Yurchenko vault is made of a run up, round off entry onto the spring board, back flick onto the vaulting table and at least one and a half somersault rotations before landing on the feet (FIG Code of Points, 2009-2012). Sands and McNeal (1995) stated that gymnasts may profit from further real-time analyses of kinematic parameters of the Yurchenko vault for implementation in training. The aim of this study was to predict optimal performance of the Yurchenko vault based upon data from the 2011 Women`s Artistic Gymnastics World Championships. Eighteen of the best scoring Yurchenko vaults from the 2011 Women`s Artistic Gymnastics World Championships were digitised using Quintic Biomechanics software (9.03v.17) to compute temporal and kinematic components of performance using the hip as Centre of Mass estimate and video captured at 25fps. Data analysis was completed in SPSS version 17, IBM. This competition included Yurchenko variations of one and a half twists, two twists and two and a half twists in the straight layout somersault position. Correlations between post flight duration and horizontal velocity at board take off and vertical velocity at horse takeoff were positive, significant and strong (horizontal r=0.79 p<0.01, vertical r=0.89 p<0.01). There were no significant correlations between post-flight time and body angles during vaulting table contact, contrary to previous findings by (Koh & Jennings, 2007; Uzunov, 2010). However, this may be due to the variance of characteristics of the gymnasts analysed. Checks for multicollinearity of the data found no issues and so stepwise multiple regression models were developed to predict post flight time using horizontal velocity at spring board take off and vertical velocity at vaulting table take off. The first model used only vertical velocity at vaulting table take off and accounted for 79.9% of the variance in post flight time (adjusted r² = 0.799). The inclusion of horizontal velocity at board take off resulted in an additional 9.4% of the variance explained (. r² = 0.94). The final model consequently significantly improves the ability to predict post flight time in this sample and explains 87.9% of the variance (adjusted r² = 0.879, F2,15 = 62.647, p = <.001). The findings of this study in relation to vertical velocity at vaulting table take off concurs with those of Koh et al., (2003) and thus extends the conclusion of existing literature to recent elite level competition.